2020
DOI: 10.3390/bs10090142
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Role of Body Image-Related Cognitive Fusion in the Relationship between Disease Severity Perception, Acceptance and Psoriasis Disability

Abstract: Psoriasis is a long-term skin disorder without a cure, whose patients are particularly susceptible to mental health diseases. Using a sample of patients diagnosed with psoriasis, this study aimed to: (1) identify the clinical and positive psychological variables that contribute the most to psoriasis disability and (2) assess the mediator role of body image-related cognitive fusion in the relation between disease severity perception and acceptance and self-compassion, on one hand, and psoriasis disability on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Adherence W (%) = Wu/Wex × 100 (1) where: Wu = medication weight used per application = (weight dispensed-weight returned)/number of applications registered in the medication log; Wex = expected medication weight per application = 0.25 g × % BSA; BSA = body surface area. A value of 0.25 g corresponds roughly to the amount needed for each application on an area corresponding to that of the palm of the hand (1% of BSA) [30][31][32].…”
Section: Medication Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence W (%) = Wu/Wex × 100 (1) where: Wu = medication weight used per application = (weight dispensed-weight returned)/number of applications registered in the medication log; Wex = expected medication weight per application = 0.25 g × % BSA; BSA = body surface area. A value of 0.25 g corresponds roughly to the amount needed for each application on an area corresponding to that of the palm of the hand (1% of BSA) [30][31][32].…”
Section: Medication Weightmentioning
confidence: 99%
“…Psoriasis is a chronic skin disease with high psychosocial impact [1,2] that is estimated to affect 2% of the world's population but varies according to regions [3]. Most patients with mild or moderate plaque psoriasis can be managed with topical therapy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the correlation between treatment satisfaction and adherence, factors such as convenience, safety, treatment type, perceived quality of life improvements, and response time, which are positive predictors of treatment satisfaction [30], could indirectly predict treatment adherence. Patients with psoriasis have a high prevalence of several mental disorders [31,32]. Some studies have examined the reasons for psoriasis treatment adherence in patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that BDD individuals have a distorted body image and experience a high depression and suicide ideation (10). Several studies showed that individuals with BDD symptoms signi cantly have problem to cognitive fusion (11,12), body image in exibility (13), and emotional symptoms (14,15). Multiple pharmacological as well as psychological therapies are used for the treatment of BDD.…”
Section: Introductionmentioning
confidence: 99%